2017
DOI: 10.1044/2016_jslhr-s-16-0035
|View full text |Cite|
|
Sign up to set email alerts
|

Anxiety in 11-Year-Old Children Who Stutter: Findings From a Prospective Longitudinal Community Sample

Abstract: Although recognized to be associated with stuttering in clinical samples, anxiety was not higher in school-age children who stutter in a community cohort. It may be that anxiety develops later or is less marked in community cohorts compared with clinical samples. We did, however, observe higher anxiety scores in those children who stuttered and had autism spectrum disorder or learning difficulties. Implications and recommendations for research are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
23
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 43 publications
3
23
0
4
Order By: Relevance
“…, 2-3세 일반아동의 비유창성 특성 (Yairi, 1981(Yairi, , 1982, 말더듬 발생시기에 따른 비유창성 특성 (Yairi & Lewis, 1984), 말더듬 지속 및 회복집단의 비유창성 특성 (Yairi & Ambrose, 1999 Yairi, Loucks, Seery, & Throneburg, 2015;Usler, Smith, & Weber, 2017;Watts, Eadie, Block, Mensah, & Reilly, 2017), 말더듬 아동의 심리적 측면에 대한 특성연구도 이루어지고 있다 (Ambrose et al, 2015;Kefalianos et al, 2017a;Kefalianos, Onslow, Ukoumunne, Block, & Reilly, 2017b;Smith et al, 2017 Millard, Nicholas, & Cook, 2008;Riley & Ingham, 2000;Trajkovski et al, 2009;Park, Lee, & Sim, 2015 (Buhr & Zebrowski, 2009;Hall, Amir, & Yairi, 1999;Hilger, Zelaznik, & Smith, 2016;Kloth, Janssen, Kraaimaat, & Brutten, 1998;Kloth, Kraaimaat, Janssen, & Brutten, 1999;Paden, Ambrose, & Yairi, 2002;Ryan, 2001;Throneburg & Yairi, 2001;Wagovich, Hall, & Clifford, 2009;Yairi & Ambrose, 1999 (Buhr & Zebrowski, 2009;Hall et al, 1999;Kloth et al, 1998Kloth et al, , 1999Ryan, 2001;Throneburg & Yairi, 2001;Yairi & Ambrose, 1999 Hall et al, 1999;Kloth, Janssen, Kraaimaat, & Brutten, 1995;Kloth et al, 1998…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…, 2-3세 일반아동의 비유창성 특성 (Yairi, 1981(Yairi, , 1982, 말더듬 발생시기에 따른 비유창성 특성 (Yairi & Lewis, 1984), 말더듬 지속 및 회복집단의 비유창성 특성 (Yairi & Ambrose, 1999 Yairi, Loucks, Seery, & Throneburg, 2015;Usler, Smith, & Weber, 2017;Watts, Eadie, Block, Mensah, & Reilly, 2017), 말더듬 아동의 심리적 측면에 대한 특성연구도 이루어지고 있다 (Ambrose et al, 2015;Kefalianos et al, 2017a;Kefalianos, Onslow, Ukoumunne, Block, & Reilly, 2017b;Smith et al, 2017 Millard, Nicholas, & Cook, 2008;Riley & Ingham, 2000;Trajkovski et al, 2009;Park, Lee, & Sim, 2015 (Buhr & Zebrowski, 2009;Hall, Amir, & Yairi, 1999;Hilger, Zelaznik, & Smith, 2016;Kloth, Janssen, Kraaimaat, & Brutten, 1998;Kloth, Kraaimaat, Janssen, & Brutten, 1999;Paden, Ambrose, & Yairi, 2002;Ryan, 2001;Throneburg & Yairi, 2001;Wagovich, Hall, & Clifford, 2009;Yairi & Ambrose, 1999 (Buhr & Zebrowski, 2009;Hall et al, 1999;Kloth et al, 1998Kloth et al, , 1999Ryan, 2001;Throneburg & Yairi, 2001;Yairi & Ambrose, 1999 Hall et al, 1999;Kloth, Janssen, Kraaimaat, & Brutten, 1995;Kloth et al, 1998…”
mentioning
confidence: 99%
“…Comparison of study typesAmbrose et al, 2015;Kefalianos et al, 2017aKefalianos et al, , 2017bShimada, Toyomura, Fujii, & Minami, 2018;Watts et al, 2017), 집단 간 특성 비교연구는 2편(25%; 예:Smith et al, 2017;Usler et al, 2017), 말더듬 집단 내 특성은 1편(13%; 예: Franken, Koenraads, Holtmaat, & van der Schroeff, 2018)으로 나타났다.…”
unclassified
See 1 more Smart Citation
“…Comparison of adults who stutter with and without social anxiety disorder 6 failed to find heightened anxiety scores in school age children who stutter (Messenger, Packman, Onslow, Menzies & O'Brian, 2015;Smith et al 2017).…”
Section: Stuttering and Social Anxiety Disordermentioning
confidence: 99%
“…A recent study by Iverach and colleagues (2016) reported that school-age children who stutter have a six-fold increased odds for social anxiety disorder and seven-fold increased odds for generalized anxiety. Results from one investigation showed higher rates of generalized anxiety among school-age boys who stutter when compared to typically fluent controls , while most other studies of childhood anxiety in the stuttering population have found no such group differences (Craig & Hancock, 1996;Ortega & Ambrose, 2011;K. A. Smith et al, 2017).…”
Section: Social Anxiety and Stutteringmentioning
confidence: 88%